Pengaruh Pemberian Brusein A dari Biji Buah Makasar (Brucea javanica L. Merr) terhadap Kematian Larva Culex quinquefasciatus Say - Destyana Ayu Wulandari; Retno Hestiningsih; Lintang Dian Saraswati; Sri Rahayu (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: This study aims to determine the effect of brusein A from Macassar fruit seeds (Brucea javanica (L) Merr) on the death of larvae Cx. quinquefasciatus Say.Methods: This research was an explanatory research using experimental method with post test only control group design. The sample was larvae Cx. quinquefaciatus Say. The distribution of the sample treatment and control groups was done randomly. Data analysis using Probit to determine the value of LC50, LC90, LT50, LT90. Further tests use ANOVA if the data are normally distributed and homogeneous, but if the data is not normally distributed or not homogeneous using Kruskal wallis.Result: The results showed that the highest percentage of Culex quinquefasciatus Say larvae mortality after administration of various concentrations of brusein A compared with temefos was at a concentration of 27 ppm, which was 55.29 percent. The higher the concentration, the higher the percentage of Culex quinquefasciatus Say deaths. The highest percentage of deaths after administration of various brusein A concentrations takes 24 hours, namely 91.13 percent. The longer time used, the higher the percentage of Culex quinquefasciatus Say deaths. LC50 was 18.833 ppm. LC90 was 68,852 ppm. The LT50 value was 437,639 minutes or 7 hours 18 minutes. The LT90 value was 1103.403 minutes or 18 hours 23 minutes. There was a difference in the average number of deaths in the brusein A concentration group (p=0.000).Conclusion: There was a difference in the average number of deaths of Culex quinquefasciatus Say larvae in the time group (p=0.000). So, there is the influence of the administration of brusein A isolated from Makasar fruit seeds (Brucea javanica (L) Merr) against the death of larvae Cx. quinquefasciatus Say.